Four new species of Triorla Parks (Diptera, Asilidae, Asilinae) from Brazil - Castro, Ivan; Bravo, Freddy; Vieira, Rodrigo (Revista Brasileira de Entomologia, 2016)
Triorla Parks has been reported from the Nearctic and Neotropical regions with 10 described species: T. ambigua (Macquart), T. argyrogaster (Macquart), T. demifasciata (Macquart), T. interrupta (Macquart), T. nervosa (Macquart), T. parastriola Pamplona & Aires, T. rubidiventris (Macquart), T. spinosa Tomasovic, T. striola (Fabricius), and T. trichina Tomasovic. Two species, T. striola and T. parastriola, have been recorded from Brazil. This paper describes four new species of Triorla from Brazil: T. beckeri sp. nov., T. milineae sp. nov., T. paraensis sp. nov., and T. spatulata sp. nov., and includes comments on the morphology of T. parastriola. An identification key to the species of Triorla is provided. © 2016 Sociedade Brasileira de Entomologia.